The Effect of Complaint Handling and Service Quality on Trust and Satisfaction of Dhyana Pura University Students - ADINEGARA, Gusti Ngurah Joko; PUTRI, Ni Kadek Theressa; KOMALASARI, Yeyen; JUNAEDI, I Wayan Ruspendi (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:The success of the teaching and learning process in today's world of education can be seen through the learning outcomes achieved by each student. Students have a vital role and are considered vital in higher education institutions. For this reason, fostering trust and maintaining student satisfaction are essential aspects of a university's development. This study aims to determine the effect of complaint handling and service quality on the trust and satisfaction of Dhyana Pura University students. Methodology :The sample was taken using the Slovin formula technique of 94 students, and the data analysis technique used was quantitative analysis, using the alternative Structural Equation Modeling (SEM) method of Partial Least Square (PLS). Findings :The results of the analysis show that the complaint handling variable has a positive and significant effect on student trust and satisfaction, service quality has a positive and significant effect on student trust and satisfaction, and trust mediates the relationship between complaint handling and service quality with student satisfaction at Dhyana Pura University. Implication :The university can use these results to maintain student trust and satisfaction by understanding how each variable affects one another. Undhira must pay close attention to handling appropriate complaints and providing quality services for each student.